Common and Not-So-Common Pathologic Findings of the Gastrointestinal Tract of Rhesus and Cynomolgus Macaques. (July 2022) - Johnson, Amanda L.; Keesler, Rebekah I.; Lewis, Anne D.; Reader, J. Rachel; Laing, Steven T.
Rhesus and cynomolgus macaques are the most frequently used nonhuman primate (NHP) species for biomedical research and toxicology studies of novel therapeutics. In recent years, there has been a shortage of laboratory macaques due to a variety of competing factors. This was most recently exacerbated by the surge in NHP research required to address the severe acute respiratory syndrome (SARS)-coronavirus 2 pandemic. Continued support of these important studies has required the use of more varied cohorts of macaques, including animals with different origins, increased exposure to naturally occurring pathogens, and a wider age range. Diarrhea and diseases of the gastrointestinal tract are the most frequently occurring spontaneous findings in macaques of all origins and ages. The purpose of this review is to alert pathologists and scientists involved in NHP research to these findings and their impact on animal health and study endpoints, which may otherwise confound the interpretation of data generated using macaques.